The Model Development of Volleyball Thrower - Wahyudi, Agung (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to create ball thrower which is utilized for motor skill practice for volleyball athletes. This research utilized qualitative approach, and major data gained through observation, interview and documentation. The procedure used was research and development model by Borg and Gall, which contains of 10 steps as follow: (1) information research and collection, (2) planning (3) developing product’ initial form, (4) initial field test, (5) major product revision, (6) major field test, (7) operational product revision, (8) operational field test, (9) final product revision, (10) dissemination and implementation. Ball thrower tool model can be used for motor skill practice, safe and secure as well as improving practice result. Volleyball AW_2016 Launcher tool models can be used to exercise the skills of volleyball athletes for motion.